2021
DOI: 10.4187/respcare.09063
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in Mechanically Ventilated Patients With SARS-CoV-2-ARDS: Focus on Tracheomalacia

Abstract: BACKGROUND:The SARS-CoV-2 pandemic increased the number of patients needing invasive mechanical ventilation, either through an endotracheal tube or through a tracheostomy. Tracheomalacia is a rare but potentially severe complication of mechanical ventilation, which can significantly complicate the weaning process. The aim of this study was to describe the strategies of airway management in mechanically ventilated patients with respiratory failure due to SARS-CoV-2, the incidence of severe tracheomalacia, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Un estudio observacional de pacientes con distrés respiratorio en ventilación mecánica invasiva, reportó que aproximadamente el 5% de ellos son diagnosticados con traqueomalacia, ocasionada muchas veces por un pequeño estrechamiento en la luz de la tráquea, causando disminución significativa del flujo de entrada de aire (10).…”
Section: Discussionunclassified
“…Un estudio observacional de pacientes con distrés respiratorio en ventilación mecánica invasiva, reportó que aproximadamente el 5% de ellos son diagnosticados con traqueomalacia, ocasionada muchas veces por un pequeño estrechamiento en la luz de la tráquea, causando disminución significativa del flujo de entrada de aire (10).…”
Section: Discussionunclassified
“…One study identified 8 of 151 patients (5.3%) developing tracheomalacia after prolonged intubation for COVID-19. 3 The mean time to diagnosis of tracheomalacia was 27 days after intubation, and all were treated with tracheostomy. The patients in our case series developed the need for emergent tracheostomy at a mean of 23 days after intubation, which may reflect similar pathology.…”
Section: Discussionmentioning
confidence: 99%
“…24 Evidence concerning the frequency of tracheostomy creation is not known, but the available research strongly suggests that intentional tracheostomy is the most frequent scenario underlying irritant contact dermatitis due to respiratory secretions. [25][26][27] For example, Fischler and colleagues 25 evaluated 90,412 patients receiving care for a combined 243,921 days in intensive care units (ICUs). They found that 10% of patients who required ventilation for more than 24 hours underwent tracheostomy.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…[28][29][30] For example, Pereira and colleagues 28 examined residents of 33 skilled nursing facilities and reported that 3.36% had longterm tracheostomies. Guarnieri and colleagues 27 evaluated 209 patients with amyotrophic lateral sclerosis and reported that 16% had a tracheostomy. Similarly, Branco's group 30 reviewed medical records of 5265 patient with cervical spinal cord injuries and reported that 20.6% required long-term tracheostomy for ventilatory support.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation